The impact of international Accounting Standard No (21) in reducing tax obstacles : applied research in the General Authority for Taxes . (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aimed to shed light on the impact of international Accounting Standard No (21) on tax obstacles represented by (tax evasion, double taxation) The financial statements of a group of banks operating in the private sector were relied upon to know the impact of the standard on tax obstacles, as well as knowing the amount of amounts, The researcher relied on the method of financial analysis of that data, which was obtained from the website of the Securities Commission, and conducted personal interviews with a number of university professors, chartered accountants, financial experts, banks, and the General Authority for Taxes to benefit from their opinions and information that enriched the research.